Gênese do caráter coeso: relação da resistência tênsil com atributos físicos e químicos do solo - Silva, Cillas Pollicarto da (2019)
The genesis of the cohesive character in soil horizons is attributed to several processes, many of which have not yet been fully clarified, hence the need for further research aiming at its elucidation. The present study aimed to evaluate the contribution of the size of sand fraction constituents and of silicon, aluminum and iron associated with poorly crystallized compounds to the cementation of cohesive horizons, as well as to define the variability of tensile strength within the same soil horizon. In the states of Ceará, Pernambuco and Bahia, horizons with and without cohesive character were selected in six soil profiles and samples in the form of blocks (15 cm wide x 20 cm long x 10 cm high) were collected at their top, middle and base positions. Aggregates/clods were obtained from the collected material and subjected to the tests of tensile strength and, subsequently, particle size with sand fractionation, and soil density. In addition, the contents of total organic carbon, as well as silicon, iron and aluminum constituting poorly crystalline oxides were quantified. Data analysis was carried out considering a completely randomized design, in a 6 x 2 x 3 factorial arrangement (six soils, two degrees of cohesion, three positions in the profile), with five replicates. F test was used in the analysis of variance and Tukey test at 5% significance level was used for means comparison. The relationship between tensile strength and sand, silt and clay fractions was measured by regression analysis (considering the linear regression model) and correlation analysis. T test at 5% significance level was used to evaluate the angular (b) and correlation (r) coefficients. As for the results, it was observed that in all horizons (with and without cohesive character) the sand fraction was predominant, defining along with the fractions silt and clay textures that ranged from sandy clay loam to sandy clay. Regarding sand fractionation, the horizons investigated in the state of Ceará, at the three positions (top, middle and base), showed predominance of fine sand followed by medium, coarse and very fine sand; horizons analyzed in the states of Pernambuco and Bahia, at the top, middle and base positions, had predominance of medium sand, followed by fine, coarse, very fine and very coarse sand. In regard to tensile strength, the values were higher in cohesive horizons, reaching 49.9 kPa, followed by the values of non-cohesive horizons (mean of 34.1 kPa). Silicon and aluminum contents were higher in horizons with cohesive character, but iron did not follow the same trend. It was concluded that tensile strength is directly associated with soil cohesion. In relation to particle size, it does not explain by itself the genesis of the cohesive character, but the poor selection of the grains of the sand fraction contributes to the denser packing of particles, resulting in a significant increase in the cohesion of aggregates/clods. Silicon and aluminum contents associated with poorly crystalline compounds contribute to the genesis of cohesion as a diagnostic attribute. There is variability of tensile strength, especially in the horizons described with the cohesive character, with reduction of cohesion from the top to the base.